Heavy Metal Removal from Aqueous Solution by Tamarind and Neem Leaves - Sivakumar, K.K.; Balamurugan, C.; Ramakrishnan, D.; Dheenadayalan, M.S. (Asian Journal of Chemistry, 2012)
In this paper, biosorption of heavy metals by biosorbents such as tamarind leaves and neem leaves were studied for effluent treatment. The residual metallic ion concentrations were determined using an atomic absorption spectrophotometer. The results obtained after 150 min contact period showed that biosorbents such as tamarind leaves and neem leaves achieved the per cent removal of 64.8, 68.2, 64.5, 55.6 and 42.5 respectively for tamarind leaves and 61.2, 64.6, 61, 52.4 and 39.4 respectively for neem leaves for copper, zinc, nickel, chromium and lead ions respectively. The ability of biosorbents to adsorb metals ions as shown from the results can be used for the development of an efficient, clean and cheap technology for textile dyeing and bleaching effluent treatment along with solar evaporation.